Forced convection heat transfer performance of TiO2-SiO2 nanofluids with wire coil inserts - Khamisah, Abdul Hamid (2019)
Heat transfer enhancement technique through compound method has been explored in the past few years with the use of nanofluids and inserts. However, studies on hybrid nanofluids with wire coil inserts are limited in the literature. The hybrid nanofluids provide better heat transfer fluids due to its advantages in stability and thermal properties. The wire coil is the best option among the swirl devices which provides maximum heat transfer enhancement and minimum friction penalty to the system. The objective of the present study is to investigate the thermo-physical properties, heat transfer and thermal hydraulic performance of TiO2-SiO2 nanofluids in water/EG mixture with wire coil inserts. Initially, the TiO2-SiO2 nanofluids were prepared at different composition ratios of 20:80, 40:60, 50:50, 60:40 and 80:20 (ratio of TiO2 to SiO2 in volume percent) for a constant 1.0% volume concentration. Later, the hybrid nanofluids were prepared at different volume concentrations from 0.5 to 3.0% for optimum composition ratio. The thermal conductivity and dynamic viscosity of nanofluids were measured using analytical laboratory equipment, whereas the density and specific heat were estimated using existing mixture relation from literature. The forced convection heat transfer investigation was conducted using the modified experimental setup and undertaken for a wide range of Reynolds number from 2,300 to 12,000 and bulk temperature of 30 °C. The experiment was undertaken at constant heat flux boundary conditions for flow in a tube with wire coil inserts at pitch ratio P/D from 0.83 to 4.17. The theoretical model was developed from van Driest eddy diffusivity equation. The evaluation on coefficient K and Prandtl index, ζ is conducted to observe their turbulent characteristics. Among five composition ratios, the ratio of 20:80 (denoted as R=0.2) was observed to be the most effective composition ratio according to the evaluation of thermo-physical properties and heat transfer performance at different composition ratios. The thermal conductivity, dynamic viscosity and heat transfer coefficient for R=0.2 at 3.0% volume concentration were increased up to 22.83%, 68.47% and 50.99%, respectively. For flow in a tube with wire coil inserts, the heat transfer enhancement was recorded up to 254.44% at 2.5% volume concentration and 0.83 pitch ratio. The friction factor insignificantly increased with the increase of volume concentration for flow in a tube without wire coil inserts. However, the friction factor of nanofluids increased from 1.88 to 6.38 times higher than water/EG in a tube for flow in a tube with wire coil inserts. The thermal performance factor (TPF) for flow of nanofluids over wire coil inserts was obtained in the range of 1.3 to 2.06. The heat transfer performance and friction factor of the nanofluids increased when the wire coil pitch ratio decreased from 4.17 to 0.83. The TPF of the TiO2-SiO2 nanofluids at all volume concentrations and different wire coil pitch ratios obtained ratio greater than one. However, the optimum condition for nanofluids with wire coil inserts occurred at 2.5% volume concentration and 1.5 pitch ratio with TPF up to 2.06. The theoretical models were validated with the experimental data and successfully predicted the turbulent characteristics of nanofluids flow with wire coil inserts. The comparison between theoretical estimation and experimental results showed a good agreement hence confirming the validity of the proposed model. Finally, it was recommended to formulate the TiO2-SiO2 nanofluids with composition ratio 20:80 for application in various heat transfer systems and prepare the nanofluids at 2.5% volume concentration with 1.50 wire coil pitch ratio for optimum performance.